(untitled) (Chemical Engineering Research Bulletin, 2010)
Sulphanilic acid and sulphanilamide schiff bases have been synthesised and evaluated as inhibitors for mild steel corrosion in 1M H2SO4 by electrochemical and non electrochemical techniques. The inhibition efficiency increases with inhibitor concentration and decreases with temperature. The adsorption of the inhibitors on the mild steel surface obeys Langmuir and Temkin adsorption isotherms. Potentiodynamic polarization studies show that the inhibitors behave as mixed inhibitors. Addition of halide ions enhances the inhibition efficiency Keywords: Sulpha Schiff bases, potentiodynamic polarization, A.C. impedence, corrosion inhibitors DOI = 10.3329/cerb.v14i1.3766 Chemical Engineering Research Bulletin 14 (2010) 1-6